Mitochondrial Functions Are Compromised in CD4 T Cells From ART-Controlled PLHIV - Zhao, Juan; Schank, Madison; Wang, Ling; Li, Zhengke; Nguyen, Lam Nhat; Dang, Xindi; Cao, Dechao; Khanal, Sushant; Nguyen, Lam Ngoc Thao; Thakuri, Bal Krishna Chand; Ogbu, Stella C.; Lu, Zeyuan; et al. (Frontiers in Immunology, 2021)
The hallmark of HIV/AIDS is a gradual depletion of CD4 T cells. Despite effective control by antiretroviral therapy (ART), a significant subgroup of people living with HIV (PLHIV) fails to achieve complete immune reconstitution, deemed as immune non-responders (INRs). The mechanisms underlying incomplete CD4 T cell recovery in PLHIV remain unclear. In this study, CD4 T cells from PLHIV were phenotyped and functionally characterized, focusing on their mitochondrial functions. The results show that while total CD4 T cells are diminished, cycling cells are expanded in PLHIV, especially in INRs. HIV-INR CD4 T cells are more activated, displaying exhausted and senescent phenotypes with compromised mitochondrial functions. Transcriptional profiling and flow cytometry analysis showed remarkable repression of mitochondrial transcription factor A (mtTFA) in CD4 T cells from PLHIV, leading to abnormal mitochondrial and T cell homeostasis. These results demonstrate a sequential cellular paradigm of T cell over-activation, proliferation, exhaustion, senescence, apoptosis, and depletion, which correlates with compromised mitochondrial functions. Therefore, reconstituting the mtTFA pathway may provide an adjunctive immunological approach to revitalizing CD4 T cells in ART-treated PLHIV, especially in INRs.